2013
DOI: 10.1371/journal.pone.0052317
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Support for the Association between Facial Shape and Aggression: A Reappraisal Based on a Worldwide Population Genetics Perspective

Abstract: Antisocial and criminal behaviors are multifactorial traits whose interpretation relies on multiple disciplines. Since these interpretations may have social, moral and legal implications, a constant review of the evidence is necessary before any scientific claim is considered as truth. A recent study proposed that men with wider faces relative to facial height (fWHR) are more likely to develop unethical behaviour mediated by a psychological sense of power. This research was based on reports suggesting that sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 42 publications
(43 reference statements)
3
50
1
Order By: Relevance
“…This measure is not invariant with respect to image variation, because variables such as expressions, head tilt, and face orientation can change the ratio. Furthermore, it was determined that the measure is not sexually dimorphic (Kramer et al 2012, Lefevre et al 2012, and there have been several failures to replicate the finding that it predicts aggressive behavior (Deaner et al 2012, Gómez-Valdés et al 2013. The authors who initially reported the latter effect recently reported that this is only the case for men with low social status (Goetz et al 2013).…”
Section: Accuracy Of Social Attributions From Facesmentioning
confidence: 99%
“…This measure is not invariant with respect to image variation, because variables such as expressions, head tilt, and face orientation can change the ratio. Furthermore, it was determined that the measure is not sexually dimorphic (Kramer et al 2012, Lefevre et al 2012, and there have been several failures to replicate the finding that it predicts aggressive behavior (Deaner et al 2012, Gómez-Valdés et al 2013. The authors who initially reported the latter effect recently reported that this is only the case for men with low social status (Goetz et al 2013).…”
Section: Accuracy Of Social Attributions From Facesmentioning
confidence: 99%
“…For example, the same behavior can be interpreted as assertive or unconfident depending on the perceived dominance of an accompanying face (7), and inferences of competence based on facial cues have even been shown to predict election results (8). Nonetheless, support for the validity of these first impressions of faces is inconclusive (9)(10)(11)(12)(13)(14)(15), raising the question of why we form them so readily.…”
mentioning
confidence: 99%
“…A third interpretation is that associations between fWHR and performance occur by chance [7,15]. Assessing the validity of these various perspectives is possible with additional data collection and analysis.…”
mentioning
confidence: 99%